DISKURSUS TENTANG TIPOLOGI HADIS DALAM KEHIDUPAN MASYARAKAT (Studi Analisis terhadap Keberadaan Hadits Maudhu'i) - Abd. Majid Abd. Majid (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2017)
It is unfortunate that the hadith which actually comes from the Messenger of Allah (saws) is marred by the emergence of hadiths of maudhu (false) that are deliberately fabricated by certain people with diverse motives and purposes, and is disseminated in the midst of society by some with a variety of purposes as well. Believing and practicing hadith maudhu is a big mistake, because although there are hadith maudlu whose contents are good, but most of the false hadith is contrary to the spirit and spirit of Islam, besides the making of hadith maudlu is a lie to the Prophet Muhammad. The spread of Hadith Maudhu 'in the midst of society, although there are hadith maudhu' which is good, but many of which bring negative impact (effect), one of them is to cause and sharpen the division among Muslims. In addition to spreading the spreading spreading of false traditions in the community can also lead to erroneous beliefs, the emergence of worship belonging to heresy, and also can turn off the sunnah. Therefore, as we are scientific in the cases of the world, we must also be scientific in the case of religion. Do not take a law or shari'ah that comes from weak hadith let alone false hadith. Or follow-up spread false and false hadiths without explaining the hadith's status.